Optimisation of soxhlet extraction parameters of hibiscus rosa sinensis using RSM: effects on yield, antioxidant activity, and morphological characteristics - Johari, Nur Syafiqah; Ismail, Nor Fariza; Yacob, Nurul Hazirah (Universiti Teknologi MARA Cawangan Pulau Pinang, 2025)
Hibiscus rosa-sinensis (HRS), a member of the Malvaceae family, is traditionally used in folk medicine and is notably rich in bioactive phytochemicals such as phenolics, flavonoids, and anthocyanins with strong antioxidant potential. Despite its phytochemical importance, limited studies have applied Soxhlet extraction to optimise the recovery of these compounds and evaluate their antioxidant activity. This study aimed to maximise the oil yield and antioxidant properties of HRS flowers by employing Soxhlet extraction in combination with Response Surface Methodology (RSM). A three-factor, three-level Box–Behnken design (BBD) was applied to evaluate the effects of solid-to-solvent ratio, particle size, and extraction time on extraction yield, DPPH scavenging activity, total phenolic content (TPC) and total flavonoid content (TFC). Post-extraction morphological alterations were further examined using Scanning Electron Microscopy (SEM). The optimised conditions—500 μm particle size, 300 mL solvent, and 180 min extraction—yielded 39.03% oil, with DPPH antioxidant activity values of 96.8%, 171.06 mg GAE/10 g TPC, and 1076.35 QE/10 g TFC. Analysis indicated that extraction time and solid-to-solvent ratio were positively correlated with oil yield and antioxidant responses, whereas particle size was inversely correlated. SEM micrographs confirmed notable surface disruption of the extracted flowers, characterised by weakened bonds and loss of cell wall integrity, supporting the efficiency of solvent penetration under optimised conditions. In summary, Soxhlet extraction combined with RSM proved effective in optimising oil yield and antioxidant recovery from HRS flowers. The findings highlight the significance of particle size, solvent ratio, and extraction duration in enhancing bioactive compound extraction, while also providing morphological evidence of structural degradation. This study demonstrates Soxhlet extraction coupled with RSM as a viable method for maximising oil yield and antioxidant recovery from HRS, though the structural integrity of the biomass is compromised.